SOLAR POWERED VENTILATOR FOR TOFU MAKERS IN GONDANGLEGI MALANG - ali mustofa (Journal of Innovation and Applied Technology, 2017)
A considerable amount of tofu production whether small or medium scale industry level has been easily found both in villages and cities. Tofu can be produced via traditional or modern process. The modern tofu processing consequently requires large investment but relatively environmentally friendly. Traditional tofu processing exploits firewood hence emits smoke and generates excessive heat in a confined space. This community service designed to assist tofu makers in Gondanglegi in reducing internal smoke and heat on production processes by building economic solar ventilator.